Analysis in the Implementation of Value Added Tax (VAT) and The Impact to Cooperative â€œXâ€ Financial Statement - Andriyani, Sinta (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study tends to understand about the implementation, payment, and reporting of Value-added Tax in Cooperative â€œXâ€. It is also aimed to explore the accounting treatment and its effect on the financial statement. To reach this goal, a researcher use qualitative method. Data is taken by Case Study approach with do some documentation, observation, interview, and literature study from the research object. The result conclude that the company has properly fulfilled the obligation of Value-added Tax and appropriately reported it based on Value-added Tax Act. However, Cooperative â€œXâ€ is still has not yet acknowledged Value-added Tax of consignment goods, doing some improper conduct at making entries, classifying tax obligation account, and the absence of input and output tax. These conduct resulted in financial statement especially Balance Sheet statement. Keywords : VAT Implementation, VAT Payment, VAT Reporting, VAT Accounting, Financial Statement